(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The results of the feasibility studies are affected by many factors, including internal and external, and here the investment climate factors represent the external factors that affect the amount of costs and profits of the investment project, which is based on the investment decision, either by rejecting or continuing the project; And through the results of the research, it was found that the cement project is considered a successful project, but the deterioration of the investment climate has hindered its implementation, and because of the difficulties faced by the investor, it contributed to the delay in the implementation of the project. The most important thing recommended by the research is the development of investment policies with achievable goals in addition to the development of clear and applicable laws in order to contribute to creating a good investment climate and contribute to the success of feasibility studies, and reduce administrative red tape and other investment obstacles that cause an increase in the costs of the investment project and thus are reflected in the results Feasibility studies.